|
\documentclass{article}
|
|
\usepackage[utf8]{inputenc}
|
|
\usepackage{amsfonts}
|
|
\usepackage{amsthm}
|
|
\usepackage{amsmath}
|
|
\usepackage{enumerate}
|
|
\usepackage{hyperref}
|
|
\hypersetup{
|
|
colorlinks,
|
|
citecolor=black,
|
|
filecolor=black,
|
|
linkcolor=black,
|
|
urlcolor=black
|
|
}
|
|
|
|
% custom solution environment to set custom numbers
|
|
\theoremstyle{definition}
|
|
\newtheorem{innersolution}{Solution}
|
|
\newenvironment{solution}[1]
|
|
{\renewcommand\theinnersolution{#1}\innersolution}
|
|
{\endinnersolution}
|
|
|
|
\title{Seminar exercises}
|
|
\author{ }
|
|
\date{February 2022}
|
|
|
|
\begin{document}
|
|
\maketitle
|
|
|
|
\begin{solution}{1.9}\
|
|
\begin{enumerate}[1.]
|
|
\item Let $f(a) = u$, then $g(f(a)) = g(u)$, so $g \circ f$ is a function.
|
|
\item We can see that composition of functions is associative as follows:\\
|
|
we know that $[ f \circ g](x) = f(g(x)), \forall x \in A$,\\
|
|
so,
|
|
$$(h \circ [g \circ f])(x) = h([g \circ f](x)) = h(g(f(x)))$$
|
|
\\
|
|
and
|
|
$$([h \circ g] \circ f)(x) = [h \circ g](f(x)) = h(g(f(x)))$$
|
|
Then, we can see that $$h \circ (g \circ f) = h(g(f(x))) = (h \circ g) \circ f$$
|
|
\end{enumerate}
|
|
\end{solution}
|
|
|
|
\begin{solution}{1.28}\
|
|
\emph{(WIP)}\\
|
|
It is isomorphic to the cosets of the \emph{nth} roots of unity, which are $\mathbb{G}_n = \{w_k\}^{n-1}_{k=0}$, where $w_k=e^{\frac{2 \pi i}{n}}$.
|
|
\end{solution}
|
|
|
|
\begin{solution}{2.2}\
|
|
|
|
To prove that the inverse $x^{-1}$ is unique, assume $x^{-1}$ and $\tilde{x}^{-1}$ are two inverses of $x$.\\
|
|
By the definition of the inverse, we know that $x \cdot x^{-1} = e$. And by the definition of the unit element, we know that $x \cdot e = x$.\\
|
|
Then, $$x^{-1} \cdot (x \cdot \tilde{x}^{-1}) = x^{-1} \cdot e = x^{-1}$$
|
|
and $$(x^{-1} \cdot x) \cdot \tilde{x}^{-1} = e \cdot \tilde{x}^{-1} = \tilde{x}^{-1}$$
|
|
By associativity property of groups, we know that
|
|
$$x^{-1} \cdot (x \cdot \tilde{x}^{-1}) = (x^{-1} \cdot x) \cdot \tilde{x}^{-1}$$
|
|
so, $$x^{-1} \cdot e = e \cdot \tilde{x}^{-1}$$
|
|
which is $$x^{-1} = \tilde{x}^{-1}$$
|
|
So, for any $x \in G$, the inverse $x^{-1}$ is unique.
|
|
\end{solution}
|
|
|
|
\begin{solution}{2.5}\
|
|
|
|
Let $\alpha = (\begin{smallmatrix}1 & 2 & 3\\ 1 & 3 & 2\end{smallmatrix})$, $\beta = (\begin{smallmatrix}1 & 2 & 3\\ 3 & 1 & 2\end{smallmatrix})$, then,
|
|
$$
|
|
\alpha \cdot \beta =
|
|
(\begin{smallmatrix}1 & 2 & 3\\ 1 & 3 & 2\end{smallmatrix})
|
|
\cdot (\begin{smallmatrix}1 & 2 & 3\\ 3 & 1 & 2\end{smallmatrix})
|
|
= (\begin{smallmatrix}1 & 2 & 3\\ 3 & 2 & 1\end{smallmatrix})
|
|
$$
|
|
|
|
and
|
|
$$
|
|
\beta \cdot \alpha =
|
|
(\begin{smallmatrix}1 & 2 & 3\\ 3 & 1 & 2\end{smallmatrix}) \cdot
|
|
(\begin{smallmatrix}1 & 2 & 3\\ 1 & 3 & 2\end{smallmatrix})
|
|
= (\begin{smallmatrix}1 & 2 & 3\\ 2 & 1 & 3\end{smallmatrix})
|
|
$$
|
|
|
|
So, we can see that
|
|
$$
|
|
(\begin{smallmatrix}1 & 2 & 3\\ 3 & 2 & 1\end{smallmatrix})
|
|
\neq
|
|
(\begin{smallmatrix}1 & 2 & 3\\ 2 & 1 & 3\end{smallmatrix})
|
|
$$
|
|
|
|
so, $\alpha \cdot \beta \neq \beta \cdot \alpha$.
|
|
\end{solution}
|
|
|
|
\begin{solution}{2.26}\
|
|
|
|
We want to prove that $f: G \rightarrow H$ is a \emph{monomorphism} iff $\ker f=\{e\}$.\\
|
|
We know that $f$ is a \emph{monomorphism} (\emph{injective}) iff $\forall a, b \in G$, $f(a) = f(b) \Rightarrow a = b$.\\
|
|
Let $a, b \in G$ such that $f(a)=f(b)$. Then
|
|
$$f(a) f(b)^{-1} = f(b) (f(b))^{-1} = e$$
|
|
$$f(a) f(b^{-1}) = e$$
|
|
$$f(ab^{-1}) = e$$
|
|
as $\ker f = \{e\}$, then we see that $ab^{-1}=e$, so $a=b$. Thus $f$ is a \emph{monomorphism}.
|
|
\end{solution}
|
|
|
|
\end{document}
|